Криоконцервация жобасындағы мектеп оқушыларының үлесі - Турсунова, Р.К. (My University, 2016)
Inourstudiesontheeffectofdifferentmethodsofcryopreservationontheintegrityofthecytoplasmic membrane of oocytes at metaphase of meiosis II revealed that the application of the balanced MPII oocyte cryopreservation using DMSO as cryoprotectant 1.5 has seen a large number of oocytes with cytoplasmic membrane damage, which can lead to cell death. The results showed that the most effective way to maintain the integrity of the membranes of eggs after freezing and thawing method was found in the application of the method of vitrification, in which there is the least percentage of damage of the cytoplasmic membrane of oocytes.
Keywords: DMSO-dimethyl sulfoxide; DPBS-Dulbecco's phosphate-buffered saline; COC-oocytecumulus complex; EG -ethylene glycol